Ionic Liquid-Based Surfactants: Recent Advances in Their Syntheses, Solution Properties, and Applications - El Seoud, Omar A.; Keppeler, Nicolas; Malek, Naved I.; Galgano, Paula D. (Polymers, 2021)
The impetus for the expanding interest in ionic liquids (ILs) is their favorable properties and important applications. Ionic liquid-based surfactants (ILBSs) carry long-chain hydrophobic tails. Two or more molecules of ILBSs can be joined by covalent bonds leading, e.g., to gemini compounds (GILBSs). This review article focuses on aspects of the chemistry and applications of ILBSs and GILBSs, especially in the last ten years. Data on their adsorption at the interface and micelle formation are relevant for the applications of these surfactants. Therefore, we collected data for 152 ILBSs and 11 biamphiphilic compounds. The head ions of ILBSs are usually heterocyclic (imidazolium, pyridinium, pyrrolidinium, etc.). Most of these head-ions are also present in the reported 53 GILBSs. Where possible, we correlate the adsorption/micellar properties of the surfactants with their molecular structures, in particular, the number of carbon atoms present in the hydrocarbon “tail”. The use of ILBSs as templates for the fabrication of mesoporous nanoparticles enables better control of particle porosity and size, hence increasing their usefulness. ILs and ILBSs form thermodynamically stable water/oil and oil/water microemulsions. These were employed as templates for (radical) polymerization reactions, where the monomer is the “oil” component. The formed polymer nanoparticles can be further stabilized against aggregation by using a functionalized ILBS that is co-polymerized with the monomers. In addition to updating the literature on the subject, we hope that this review highlights the versatility and hence the potential applications of these classes of surfactants in several fields, including synthesis, catalysis, polymers, decontamination, and drug delivery.